2018
DOI: 10.3324/haematol.2018.201038
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib in combination with prednisone and nilotinib exhibit synergistic effects in human cells lines and primary cells from myeloproliferative neoplasms

Abstract: Ruxolitinib is the front-line non-palliative treatment for myelofibrosis (MF). However, a significant number of patients lose or present suboptimal response, are resistant or have unacceptable toxicity. In an attempt to improve response and avoid the adverse effects of this drug, we evaluated the combination of 17 drugs with ruxolitinib in ex vivo models of peripheral blood mononuclear cells from MF patients and cell lines. We found that the combination ruxolitinib and nilotinib had a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…6,7 Given the overlapping clinical and morphologic features of MPN, it is important to test all of the mutations in JAK2/MPL/CALR and the BCR-ABL1 status in patients suspected of having MPNs. As observed in CML patients 10 and patients with coexistent BCR-ABL1 and JAK2 mutation, 11 combination treatment with TKI and ruxolitinib in our patient was safe and effective, which was also confirmed by three previous patients with coexistent BCR-ABL1 and CALR mutation, one treated with imatinib/dasatinib and ruxolitinib 3 and the others with imatinib and ruxolitinib 4,5 Moreover, recent studies found that the combination of ruxolitinib and nilotinib had a synergistic effect against both CML stem cells 12 and MF cells, 13 so our combination of nilotinib and ruxolitinib may have been better for this patient. However, the CALR mutation allele burden was not decreased and the splenomegaly persisted after 18 months of ruxolitinib therapy.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Given the overlapping clinical and morphologic features of MPN, it is important to test all of the mutations in JAK2/MPL/CALR and the BCR-ABL1 status in patients suspected of having MPNs. As observed in CML patients 10 and patients with coexistent BCR-ABL1 and JAK2 mutation, 11 combination treatment with TKI and ruxolitinib in our patient was safe and effective, which was also confirmed by three previous patients with coexistent BCR-ABL1 and CALR mutation, one treated with imatinib/dasatinib and ruxolitinib 3 and the others with imatinib and ruxolitinib 4,5 Moreover, recent studies found that the combination of ruxolitinib and nilotinib had a synergistic effect against both CML stem cells 12 and MF cells, 13 so our combination of nilotinib and ruxolitinib may have been better for this patient. However, the CALR mutation allele burden was not decreased and the splenomegaly persisted after 18 months of ruxolitinib therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Since MF is a complex disease in which tyrosine-kinase-mediated signaling pathways are involved in the production of hematopoietic clones and with the fibrosis of the bone marrow, the use of drugs in combination against different targets may be beneficial. Previous data have shown that ruxolitinib combined with prednisone and nilotinib exhibits synergistic effects in human cell lines and primary cells from myeloproliferative neoplasms (MPN) [29]. Ruxolitinib showed the ability to diminish or stabilize Ruxolitinib plus nilotinib showed a synergistic behavior that blocked colony formation in patients' primary cells and inhibited the phosphorylation of STAT5 and ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Ruxolitinib plus nilotinib showed a synergistic behavior that blocked colony formation in patients’ primary cells and inhibited the phosphorylation of STAT5 and ERK1/2. In addition, the combination with prednisone increased this synergy and inhibited the synthesis of collagen in bone marrow mesenchymal cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study confirmed that therapeutic targeting of Y-Box Binding Protein 1 (YBX1)-dependent ERK signaling in combination with JAK2 inhibition could eradicate cells harboring mutations in JAK2 ( 16 ). The ruxolitinib/nilotinib/prednisone combination showed synergistic inhibitory effects on the JAK/STAT and MAPK signaling pathways in MPN cells ( 17 , 18 ). Thus, IFNα combined with JAK2 or MEK inhibition might improve therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%